A DESCRIPTIVE STUDY ON TEACHING WRITING DESCRIPTIVE TEXT USING PICTURE TO THE SECOND YEAR STUDENTS OF SMP NEGERI 1 PRAMBANAN IN 2009/2010 ACADEMIC YEAR - ASTUTI, SELVIANA IKA ANDRI (2010)
This study is aimed at describing the teaching writing descriptive text using picture. The objectives of the study are to describe the teaching writing descriptive text using picture. to the second year students of SMP N 1 Prambanan and to describe the students' ability in making descriptive text using picture to the second year students of SMP N 1 Prambana The study was implemented in SMP N 1 Prambanan, especially class 8A and 8B using a descriptive qualitative research. The writer took 65 students as the subject of the research. The data is a descriptive qualitative data and the source of data taken from event, informant and document. She uses observation, interview and document to collecting the data. The technique of analyzing data are describing the process of teaching writing using picture, presenting the students' writing about the descriptive text using picture, discussing the finding, and drawing conclusion and giving suggestion. The result of the study shows that the students' ability in making descriptive text using picture is good enough. The students can make a descriptive text using picture based on its structural elements, although there is a mistake in the component of writing. The lowest score in class 8A is 75 and the highest score is 98. The score average is 88, 07. In class 8B, the lowest score is 45 and the highest score is 100. The score average is 71, 69.